Extraintestinal traits of pathogenicity and sequence type lineages in commensal Escherichia coli from adults and young children: genotypic and phenotypic profiles - Bok, Ewa; Mazurek-Popczyk, Justyna; Wojciech, Magdalena; Baldy-Chudzik, Katarzyna (Frontiers in Microbiology, 2025)
BackgroundThe commensal Escherichia coli population may significantly influence the pathogenesis of extraintestinal infections. The assignment to specific sequence type (ST) lineages and the presence of particular combinations of virulence genes are characteristic features of extraintestinal pathogenic E. coli (ExPEC)—although not exclusively. Extraintestinal virulence genes are also identified among commensal E. coli. This study aimed to examine the genotypic and phenotypic characteristics of the extraintestinal virulence potential of two populations of commensal E. coli isolates from adults and young children.MethodsGenotypic traits were detected using polymerase chain reaction (PCR). Appropriate phenotypic assays and real-time PCR were used to analyze the expression of virulence factors. Multilocus sequence typing was performed using the seven-loci Achtman scheme.ResultsGenotypic studies revealed the virulence potential of the commensal isolates, and phenotypic analyses confirmed whether the genes are expressed. E. coli from adults carried pathogenicity islands and virulence genes in significantly higher proportions, resulting from the dominance of phylogroup B2 in this set of isolates. The hemolytic activity and higher levels of siderophore receptor expression were more common in E. coli from adults and were closely related to the dominance of phylogroup B2. Other traits not associated with phylogroup B2, such as adhesion abilities mediated by type 1 and P fimbriae and strong biofilm formation propensities, were detected with similar frequencies in both pools of isolates. E. coli harboring pathogenicity islands were subjected to multilocus sequence typing analysis. Sequence types ST73, ST59, ST131, ST95, ST141, and ST69 were most common in isolates from adults, whereas ST10, ST155, ST59, and ST1823 from children. In our collection of E. coli, the ST73 exhibited the highest potential for extraintestinal virulence.ConclusionA significant proportion of E. coli from adults compared to young children exhibited considerable virulence potential, which may enable them to function as endogenous pathogens. Our research highlights the significant accumulation of extraintestinal pathogenicity features in commensal E. coli, indicating the need to monitor genetic and phenotypic profiles in “silent” potential pathogens.